2020
DOI: 10.56686/9781732003101
|View full text |Cite
|
Sign up to set email alerts
|

Disaster Labs: How American States Use Partnerships to Manage the Unthinkable

Abstract: Disaster Labs explores how state governments partner with businesses and nonprofits to manage large-scale emergencies in California, Florida, New York, and Virginia. For these disaster- management collaborations to continue, state governments, businesses, and nonprofits must plan now for their future. These collaborations also need the freedom to shape their partnerships in each of their unique state environments. Each state has distinct attributes that make state-level partnerships attractive. These range fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…While research and debates on the pitfalls of public‐private disaster cooperation generally discuss the issue from the perspective of public authorities, highlighting implications such as profiteering, loss of transparency and accountability (Tierney, 2015), ambiguous allocation of responsibility (Bergling et al, 2016) and tensions between public and financial interests (Busch & Givens, 2013; Givens, 2020), we have shown that the involvement of private actors in disaster management is a tricky business also for private actors. Would they be paid for their involvement?…”
Section: Concluding Discussion: the Uncertain Costs Of Public–private...mentioning
confidence: 99%
See 4 more Smart Citations
“…While research and debates on the pitfalls of public‐private disaster cooperation generally discuss the issue from the perspective of public authorities, highlighting implications such as profiteering, loss of transparency and accountability (Tierney, 2015), ambiguous allocation of responsibility (Bergling et al, 2016) and tensions between public and financial interests (Busch & Givens, 2013; Givens, 2020), we have shown that the involvement of private actors in disaster management is a tricky business also for private actors. Would they be paid for their involvement?…”
Section: Concluding Discussion: the Uncertain Costs Of Public–private...mentioning
confidence: 99%
“…When the Country Administrative Board appealed to the public to donate resources it was strongly criticized in the media (Nilsson & Enander, 2020). Public-private cooperation may thus have helped the In many ways, then, this public-private cooperation was a win-win for all parties involved, in terms of no-cost marketing exposure for firms and access to scarce goods and services for public sector agencies (see Givens, 2020). However, in their mission to support the public responders as their subsuppliers, the e-volunteers became increasingly enthusiastic and hot headed.…”
Section: Safety Risks and Blurred Work Environment Responsibility For...mentioning
confidence: 99%
See 3 more Smart Citations